Recurrent giant cystic lymphangioma of peritoneum: a case report and literature review - Lei, Hongyan; Sun, Jinxin; Wang, Yongzhou; Ye, Tao (Frontiers in Oncology, 2024)
Cystic lymphangioma (CL) is a rare benign tumor of the lymphatic system, most commonly found in the neck, head, and armpits. The incidence of lymphangiomas in the abdominal cavity is less than 5%, and the incidence of retroperitoneal tumors is even lower. We report here a case of recurrent giant CL that recurred 20 years after the first complete surgical resection. Pelvic MRI at 6 months follow-up after the second complete surgical resection indicated a recurrence of the tumor. The main purpose of this article is to explore the treatment and follow-up strategies for recurrent lymphangioma.